2015
DOI: 10.1021/acsami.5b04879
|View full text |Cite
|
Sign up to set email alerts
|

Composite Films of Poly(vinyl alcohol) and Bifunctional Cross-linking Cellulose Nanocrystals

Abstract: Long and flexible cellulose nanofibrils or stiff and short cellulose nanocrystals (CNCs) are both promising lightweight materials with high strength and the potential to serve as reinforcing agents in many polymeric materials. In this study, bifunctional reactive cellulose nanocrystals (RCNCs) with carboxyl and aldehyde functionalities were used as reinforcements to prepare acetal-bonding cross-linked poly(vinyl alcohol) (PVA) films. Two RCNCs were obtained through the mechanical homogenization of partially ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 48 publications
6
43
0
1
Order By: Relevance
“…when PVA/CNC composites (1 and 2 wt %) were compared to the neat PVA . These observations have led to the conclusion that the reinforcing ability of CNCs is dominated by the interfacial interaction between the CNCs and PVA …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…when PVA/CNC composites (1 and 2 wt %) were compared to the neat PVA . These observations have led to the conclusion that the reinforcing ability of CNCs is dominated by the interfacial interaction between the CNCs and PVA …”
Section: Introductionmentioning
confidence: 98%
“…However, the poor mechanical properties of PVA limit its use . The introduction of a reinforcing material in the PVA matrix has been reported to improve its mechanical properties …”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it has been reported that the addition of nano‐sized particles can enhance the nucleation of a polymer and thus would increase the crystallinity index. The diffraction pattern of NCC‐PMAMs could not be detected in CA/NCC‐PMAM‐Cl nanocomposite films, and there was no peak shift due to the addition of NCC‐PMAM particles, which could mean that an intercalated structure might exist between CA polymer and NCC‐PMAM nanoparticles. …”
Section: Resultsmentioning
confidence: 99%
“…As is shown in Figure (a), the pure PVA had two stages of decomposition, whereas there was only a single sharp decomposition in the pure PEO. For PVA, the first decomposition region, at approximately 250–370 °C, was due to the degradation of the PVA chain, whereas the second region, at approximately 380–500 °C, was due to the carbonation of the polymer matrix and was followed by a final decomposition of the polymer . PEO exhibited only a single‐stage degradation, which occurred at approximately 367–450 °C by the random chain scission of CO bonds .…”
Section: Resultsmentioning
confidence: 99%